Long-term changes in zooplankton in the Changjiang estuary from the 1960s to 2020 - Du, Ping; Ye, Wen-Jian; Deng, Bang-Ping; Mao, Ming; Zhu, Yuan-Li; Cheng, Fang-Ping; Jiang, Zhi-Bing; Shou, Lu; Chen, Quan-Zhen (Frontiers in Marine Science, 2022)
The Changjiang estuary (CJE) is a large estuary that is affected by multiple anthropogenic stressors and climate change. The long-term trend of zooplankton in the CJE is an important indicator of the ecological response to stressors. We applied the Mann–Kendall trend analysis and Pettitt test to detect the trend and breakpoints of the biomass of the large mesozooplankton (LMZ; 505–20 000 μm) in four seasons, abundance of main LMZ taxa in summer from the 1960s to 2020, and abundance of dominant species in summer from 2000 to 2020 in the CJE. Results showed that LMZ biomass increased significantly during spring and summer, and the breakpoints both occurred in the 1980s. After the breakpoint, the mean biomass increased from 142.88 to 429.42 mg/m3 in spring and from 296.28 to 723.92 mg/m3 in summer. After 2000, the abundance of Copepoda in summer increased by more than 10 times compared to the 1960s. Under the conditions of warming and increased dinoflagellate abundance in the CJE, the abundance of the warm-water and omnivorous small calanoid copepod Paracalanus aculeatus increased significantly. Meanwhile, the significant decrease in the abundance of the temperate brackish species Labidocera euchaeta was probably mainly related to warming. The rapid changes in LMZ biomass during the late 1980s and mid-1990s is probably the result of a combination of enhanced bottom–up support, reduced top–down pressure, and promotion of temperature. This study provides scientific evidence and insights into the adaptive management of the Changjiang Basin.